ENVIRONMENTAL STARTUP IN FASHION INDUSTRY - Tarayevska, L.S.; Rishchuk, L.I. (The actual problems of regional economy development, 2021)
The article explores and analyzes environmental startups in the fashion industry, namely: the Ukrainian brand Motrya, Panove, Défi and Framiore, which became one of the eight Ukrainian innovative companies funded by the Ukrainian Startup Fund, as well as other Ukrainian startups that have conquered the market and position themselves as "eco" in the fashion industry. However, not all environmental startups in the fashion industry are successful and this is not surprising, because the things they offer us are not cheap and not always manufacturers can convey to consumers the specific values ​​that this product creates. That is why by successful value we mean not only what is beautiful, fashionable, not only the use of natural or organic materials, but the environmental friendliness and aesthetics of their processing and further operation, the use of technologies that help minimize the environmental footprint. Moreover, these startups must take care of the environmental friendliness of delivery, further processing of things as part of the production cycle, create distribution channels that will be most acceptable to a particular consumer in a given period of time and all will be financially effective. Therefore, currently, there are only a few such brands in Ukraine. After all, the creation of such a company requires considerable effort, deep philosophy, understanding of all stages. And what's worse: truly established brands mostly sell their products abroad. Therefore, in this situation it is necessary to sit down at the negotiating table with the state and prescribe rules on how to green the light industry. The advantages of implementing environmental business ideas in startups include: improving the image through environmental responsibility of doing business; increasing the competitiveness of the business entity in domestic and foreign markets; resource saving and reduction of energy consumption of production; making quality clothing that preserves naturalness is comfortable and hypoallergenic; increasing employment and population development; formation of eco-thinking and eco-culture. Thus, the policy of socially responsible business, because this is what we consider the development of environmental startups in the fashion industry, has obvious benefits for all market participants. The consumer, as a member of society, satisfies his need to be able to buy a quality, stylish, environmentally friendly and ergonomic thing. Society, in turn, receives an improvement in the environmental situation and the conservation of resources, the creation of new jobs, staff training and care for the health of employees and their families. The company is rewarded not only by creating a favorable public opinion, but also by increasing the recognition and loyalty of customers, and, consequently, by improving financial performance.